Genetic Analysis of mcr-1-Carrying Plasmids From Gram-Negative Bacteria in a Dutch Tertiary Care Hospital: Evidence for Intrapatient and Interspecies Transmission Events - Strepis, Nikolaos; Voor in ’t holt, Anne F.; Vos, Margreet C.; Zandijk, Willemien H. A.; Heikema, Astrid P.; Hays, John P.; Severin, Juliëtte A.; Klaassen, Corné H. W. (Frontiers in Microbiology, 2021)
The role of plasmids in the complex pandemic of antimicrobial resistance is increasingly being recognized. In this respect, multiple mobile colistin resistance (mcr) gene-carrying plasmids have been described. However, the characteristics and epidemiology of these plasmids within local healthcare settings are largely unknown. We retrospectively characterized the genetic composition and epidemiology of plasmids from mcr-1-positive bacterial isolates identified from patients from a large academic hospital in the Netherlands. Clinical Gram-negative bacteria with an MIC >2 µg/mL for colistin, obtained from patients hospitalized at the Erasmus MC University Medical Center Rotterdam during the years 2010-2018, were screened for presence of the mcr-1 gene. Extracted plasmids from mcr-1-positive isolates were sequenced using a combination of short- and long-read sequencing platforms, characterized by incompatibility type and genetic composition and compared to publicly available mcr-1-carrying plasmid sequences. In 21 isolates from 14 patients, mcr-1 was located on a plasmid. These plasmids were of diverse genetic background involving Inc types IncX4, IncI2(delta), IncHI2, as well as double Inc types IncHI2/IncN and IncHI2/IncQ. mcr-1-carrying plasmids were found in Escherichia coli, Klebsiella pneumoniae and Kluyvera georgiana, and within the chromosome of an ST147 K. pneumoniae isolate. In depth analysis indicated intrapatient, interpatient, and interspecies transmission events of mcr-1-carrying plasmids. In addition, our results show that the mcr-1 gene resides in a rich environment full of other (mcr-1 negative) plasmids and of many different Inc types, enabling interplasmidal transfer events and facilitating widespread dissemination of the mcr-1 gene. Multiple mcr-1-carrying plasmid transmission events had likely occurred among isolates from hospitalized patients. Recognition and identification of plasmid transmission events within hospitals is necessary in order to design and implement effective infection control measures.